Point-of-Use Simultaneous Electrochemical Detection of Lead and Cadmium Using Low-cost Screen-printed Transparency Electrodes. (2017) - Martín-Yerga, D.; Álvarez-Martos, I.; Blanco-López, M.C.; Henry, C.S.; Fernández-Abedul, M.T.
Abstract: In this work low-cost screen-printed transparency electrodes were fabricated and optimized for the simultaneous detection of lead and cadmium using square-wave anodic stripping voltammetry. Bismuth was employed in order to enhance preconcentration of the metals on the electrode surface. Transparency electrodes were integrated in sample vial caps for point-of-use detection, directly on the container where the sample is collected.